Speed of sound as a function of temperature and pressure for propane derivatives. (June 2017) - Yebra, Francisco; Zemánková, Katerina; Troncoso, Jacobo
Graphical abstract: Highlights: New speed of sound data for six propane derivatives is reported. Temperature and pressure ranges: (283.15–343.15) K and (0.1–95) MPa. Data are compared with those available for other propane derivatives. Temperature and pressure dependencies of sound speed are analyzed. Abstract: The speed of sound in the temperature and pressure intervals (283.15–343.15) K and (0.1–95) MPa was measured for nitropropane, propionitrile, 1, 2-dichloropropane, 1, 3-dichloropropane, propylamine and propionic acid. An apparatus based on the acoustic wave time of flight determination, with a fully automatized temperature and pressure control, was used to this aim. The speed of sound derivatives against temperature and pressure, as well as the nonlinear acoustic coefficient was obtained from experimental values. The results are analyzed and compared with previously reported data for other propane derivatives: propane, 1-propanol, propanone, d-propanone, and several fluoropropanes. All obtained magnitudes are rationalized basing on the physicochemical properties of these fluids. Nearness to critical point and molar mass are revealed as key factors as regards the speed of sound behavior against temperature and pressure.